Peran Pendidikan Aqidah Akhlak dalam Pembentukan Karakter Siswa Sekolah Dasar - Saribun (Jurnal Budi Pekerti Agama Islam, 2024)
Aqidah Akhlak education is the initial education or religious foundation that children must have from an early age, Aqidah Akhlak education in elementary schools has been integrated into Islamic religious education subjects. This is in accordance with the aim of education, namely to make students as human beings who fear God Almighty and have noble character. Aqidah itself refers to belief and faith in Allah SWT and its practice, and morals are habits and behaviors that depart from self-awareness both in human relationships with God, human relations and the natural environment. Character building has a meaning as an effort that is carried out in earnest to form character or behavior that can become a person's characteristics, whereas to form the character of elementary school students is not an easy thing because elementary school students have different characteristics. Therefore, this study aims to determine the extent to which the role of aqeedah moral education plays a role in building the character of elementary school students. The method used in this research is a literature study method by reviewing journals and previous research using content analysis techniques. Based on the research that has been done, the results show that aqidah moral education has a very important role in building the character of elementary school students.